Significance of Āyurvedic Trees in the Vedas - Panda, Prajñā (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
The Vedas are the oldest scriptures in this Universe and it is the source of all knowledge. These are known as the divine or origin. These Vedas contain systematic scientific knowledge as well as knowledge of the creation of the world. Every type of knowledge is available in these Vedas. The Āyurveda is a part of the Vedas and it deals with various diseases, medicines, trees, plants, etc.  Generally, the tree may be defined as a perennial plant having fully distinguishable root and shoot system. In general, they are woody with well developed vascular tissue. The earliest mention of the trees is found in the Ṛgveda, the oldest repository of human knowledge. A long hymn (X.97) of the Ṛgveda is devoted to worshipping the trees and plants with special reference to their healing properties. In the Atharvaveda or Brahma Veda trees and plants are also mentioned with special reference to their healing properties and their capacity of warding of the demons. In the Ṛgveda, the cult of trees is well recognized. Therefore, the trees were implored to bestow for good off spring, various worldly amenities and also for long life without any disease.